Confocal laser method for quantitative evaluation of critical optical properties of toric intraocular lenses. Issue 3 (March 2016) - Walker, Bennett N.; James, Robert H.; Song, Samuel; Calogero, Don; Ilev, Ilko K.
Abstract : Purpose : To present a proof‐of‐concept study on the development and implementation of an innovative confocal laser method platform for precise quantitative evaluation of critical optical properties unique to toric intraocular lenses (IOLs). Setting : U.S. Food and Drug Administration, Optical Therapeutics and Medical Nanophotonics Laboratory, Silver Spring, Maryland, USA. Design : Experimental study. Methods : The optical properties of hydrophobic toric IOLs were evaluated with a confocal laser method that was modified to isolate the 2 planes of focus that are observed with toric IOLs. Results : The results show the confocal laser method has the potential to measure the orthogonally separated optical powers and then calculate them to the commonly referenced spherical equivalent and cylinder powers of toric IOLs with high accuracy (≤1 μm of focal length measurement). Furthermore, the proposed confocal laser method design includes a new component for precise differentiation of the 2 focal planes and isolation of the 2 focal points, and thus for accurate measurement of the anterior cylinder axis of toric IOLs. Conclusion : The modifications to the confocal laser method platform enabled the quantitative evaluation of optical properties attributed to toric IOLs. Financial Disclosure : None of the authors has a financial or proprietary interest in any material or method mentioned.